The Effect of Perceived Ease of Use and Perceived Usefulness on E-WOM and Buying Intentions on Wardah Virtual Try on in Indonesia (Mediation Role of Cognitive and Emotional) - Kholifah, Cantika Nur; Dewi, Citra Kusuma (International Review of Management and Marketing, 2026)
The development of digital technology has driven brands to continuously evolve and innovate, influencing consumer shopping experiences and consumption patterns. The world of digital technology continues to develop rapidly, with advances in artificial intelligence (AI), 5G networks, the internet of things (IoT), augmented reality (AR), virtual reality (VR), big data, and mixed reality (MR). This study aims to examine the influence of perceived ease of use and perceived usefulness on e-word of mouth (e-WOM) and buying intentions in Wardah virtual try-on in Indonesia with the mediating role of cognitive and emotional factors. Based on the Technology Acceptance Model (TAM) and the Technology-Enabled Engagement (TEE) process, this study contributes by providing empirical evidence and helping to clarify the understanding of technology acceptance and consumer behavior in interactive digital marketing, as well as providing practical benefits for companies in improving user experience in order to encourage positive e-WOM and increase consumer purchase intent. The method used in this study is a descriptive quantitative research method, using purposive sampling and non-probability sampling techniques. Data was collected using a survey method with questionnaires to gather data from respondents who were users of Wardah Virtual Try On. Data analysis was performed using the partial least squares–structural equation modeling (PLS-SEM) method.